The Gulf Cooperation Council and Central Asian Countries: Vision Future (قضايا سياسية, 2022)
This research studies the relations between the countries of the Gulf Cooperation Council and the countries of Central Asia, which today are entering a new stage of development in the political, diplomatic, economic, investment, technological and military fields. This topic, the Central Asian region has been far from the interests of Arab researchers for many years, and we believe it is still today.The research deals with four main sections with conclusions and future visions. The first topic deals with the Central Asian region, the location and strategic importance, and the second topic discusses the regional players in Central Asia, namely Turkey, Iran, Israel and Pakistan, and the third topic the international players, the United States of America, Russia and China, and the fourth topic, It deals with the dimensions of relations between the countries of the Gulf Cooperation Council with the countries of Central Asia in the political, diplomatic, economic, technological and military aspects, then the research concludes to the conclusions and the future vision based on the presentation of three future scenarios for these relations.Central Asian countries believe that cooperation with the Arab Gulf states is achieving positive results for them in the economy, trade and investment, and bringing in Arab capital to achieve development in them, and that political rapprochement creates a balance that supports balance opportunities with Iran, Turkey and Pakistan, and leads to combating cross-border terrorism, and it appears clearly there. Gulf trends led in particular (Saudi Arabia and the UAE) towards Central Asian countries, and that (Uzbekistan and Kazakhstan) in particular are countries that have economic and strategic weight, and have a great desire to cooperate with the Gulf Cooperation Council countries in the future.Gulf strategic dialogue with the countries of Central Asia must be conducted to create a roadmap to remove the challenges and difficulties facing the development of relations between the two sides in the political, economic, cultural, technological, scientific and security fields, and the tourism and cultural movement with the Central Asian countries that were Islamic, urban, historical and archaeological landmarks, and vice versa must be supported. Removing challenges and barriers from the Asian tourism and cultural movement towards the Gulf capitals, because at the core of the development of inter-state relations is that of societal and not only hierarchical supremacy.